SKP2 Overexpression Is Associated With Increased Serine 10 Phosphorylation of p27 (pSer10p27) in Triple‐Negative Breast Cancer. Issue 9 (September 2014) - Fagan‐Solis, Katerina D.; Pentecost, Brian T.; Gozgit, Joseph M.; Bentley, Brooke A.; Marconi, Sharon M.; Otis, Christopher N.; Anderton, Douglas L.; Schneider, Sallie Smith; Arcaro, Kathleen F.
<x xml:space="preserve">Abstract</x> S‐phase kinase‐associated protein 2 (SKP2) is an important cell cycle regulator, targeting the cyclin‐dependent kinase (CDK) inhibitor p27 for degradation, and is frequently overexpressed in breast cancer. p27 regulates G1/S transition by abrogating the activity of cyclin/CDK complexes. p27 can undergo phosphorylation at serine 10 (pSer10p27). This phosphorylation event is associated with increased cell proliferation and poor prognosis in patients with glioma. The relationship between SKP2 and pSer10p27 in breast cancer has not been previously investigated. Immunohistochemistry (IHC) of SKP2, p27, pSer10p27, and other genes involved in this pathway, was analyzed in 188 breast tumors and 50 benign reduction mammoplasty samples. IHC showed SKP2 to be more highly expressed in estrogen receptor α (ERα)‐negative breast cancers and demonstrated that triple‐negative tumors were more likely to have high expression of SKP2 than were non‐triple negative, ERα‐negative tumors. A significant positive relationship was discovered for SKP2 and pSer10p27. High levels of SKP2 and pSer10p27 were observed significantly more often in ERα‐negative and triple‐negative than in ERα‐positive breast cancers. Use of the triple‐negative TMX2‐28 breast cancer cell line to address the role of SKP2 in cell cycle progression confirmed that SKP2 contributes to a more rapid cell cycle progression and may regulates pSer10p27 levels. Together, the results indicate that presence of high SKP2 plus high pSer10p27 levels in triple‐negative breast cancers is associated with aggressive growth, and highlight the validity of using SKP2 inhibitors as a therapeutic approach for treating this subset of breast cancers. J. Cell. Physiol. 229: 1160–1169, 2014. © 2014 Wiley Periodicals, Inc.